1998
DOI: 10.1161/01.cir.97.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenting and Angioplasty

Abstract: C arotid artery stenosis, particularly involving the origin of the internal carotid artery, is a frequent clinical problem. These stenoses, almost invariably atherosclerotic, can present as asymptomatic bruits discovered on physical examination, one or more transient ischemic attacks related to embolization of thrombus from stenotic lesions or to hypoperfusion, or less commonly, as an ischemic stroke. From the results of three high-quality prospective randomized trials, 1-3 it has become apparent that symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 18 publications
(2 reference statements)
0
7
0
1
Order By: Relevance
“…Although it has been claimed that during this period, patients should only be treated within trials, 9 the promising results reported by the majority of authors involved in CAS are leading to its increased use in everyday practice in many parts of the world. In view of this situation, the German Society of Angiology and the German Society of Radiology decided to install a registry of CAS as a measure of quality assurance and control against unrestricted use of the method.…”
mentioning
confidence: 99%
“…Although it has been claimed that during this period, patients should only be treated within trials, 9 the promising results reported by the majority of authors involved in CAS are leading to its increased use in everyday practice in many parts of the world. In view of this situation, the German Society of Angiology and the German Society of Radiology decided to install a registry of CAS as a measure of quality assurance and control against unrestricted use of the method.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] However, fear of distal embolization of plaque fragments to the brain has generated concern regarding the safety and wisdom of this approach, especially considering the established low risk and durability of endarterectomy. 17,18 The incidence of stroke generally reported with carotid stenting is 5% to 10%, [11][12][13][14][15][16] although 1 center reported stroke in 71% of an early series. 19 Transcranial Doppler studies suggest the universal occurrence of emboli associated with this procedure.…”
mentioning
confidence: 99%
“…Os pacientes com antecedente de AVC isquêmico apresentaram risco elevado de sofrer novo evento cerebrovascular da ordem de 30% a 50% em cinco anos. As diretrizes vigentes [21][22][23] recomendam a realização de ICP nos centros com índices de eventos combinados inferiores a 3% em pacientes assintomáticos (baseado no estudo Asymptomatic Carotid Surgery -ACAS 24 ) e inferiores a 6% em pacientes sintomáticos (baseado no estudo NASCET) 10 .…”
Section: Discussionunclassified